The early reception of Science and Human Behavior in Brazil - Miranda, Rodrigo Lopes; Strapasson, Bruno Angelo (Perspectivas em Análise do Comportamento, 2023)
This article historicizes the reception and circulation of Behavior Analysis in Brazil concerning the translation of the book Science and Human Behavior (S&HB) into Brazilian Portuguese. Published biographies and autobiographies, epistolary exchanges, and interviews with participants of the aforementioned history were used as primary textual sources. Secondary sources were also used. In the United States of America (USA), a nation with a long tradition of experimental psychology, S&HB was developed as a teaching resource. However, it became known and disseminated mainly for its comprehensive exposition of a science of human behavior. In Brazil, its appropriation through translation, which occurred in the first half of the 1960s, although it also had a didactic purpose, was influential in helping to consolidate the importance of the experimental foundation of a science of behavior in the context of creating the new Psychologist profession that was establishing itself in the country. S&HB was a milestone in the development of Behavior Analysis in the USA and Brazil. However, the process of appropriating the book in Brazil had its own configurations in the context of our country.